APLIKASI METODE BOUCHERI UNTUK MENGAWETKAN BAMBU SEGAR - Pipin Permadi; Ginuk Sumarni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
This paper deals with reseach results on bamboo preservation using boucherie method. Two bamboo species, namely andong (Gigantocloa verticillta Munro) and tali (Gigantochloa apus Kurtz) were treated freshly using Borax (Na2B4O7. IOH2O) solution with strenght solution of 5% as preservative. One of butt of the 8 length bamboo was immersed 10 cm in borax solution for 2. 4. 6, 8. and 10 days and the penetration of preservative were observed. The results showed that the penetration of preservative in andong bamboo for 2. 5, 6, 8, and 10 consecutively were 131,40 cm, 304,92 cm, 308.42 cm, 469,88 and 315,28 cm, while in tali, bamboo were 68,30 cm, 116.83 cm, 141,88 cm and 128,17 cm, respectively. Maximum pnetration of preservative was achived in 8 days immersion for andong and 6 days tali.